Placement of Trash Bins in The Interior of The Hospital Emergency Department to Increase Comfort, Effectiveness, and Work Efficiency - Levi Anatolia S.M. Exposto; Made Ida Mulyati (Rifa'Institute, 2022)
Hospital waste management will reduce the risk of disease for patients and paramedics. In addition, the comfort of the hospital service room (IGD) is an important element that does not only affect the image of the hospital. For this reason, it is necessary to optimize waste management in hospital services, especially in the auction room, such as the emergency room. The aim is to place the trash in the interior of the hospital emergency department to increase comfort, effectiveness, and work efficiency. The method used in conducting systematic review uses a scrum based on the PRISMA (Preferred Reporting Item for Systematic Review and Meta-Analysis) protocol which includes identification, screening, eligibility and included. From the 5 articles analyzed, it was found that health services in the ER are a very important element in dealing with patients who are in an emergency, it is necessary to maintain the ER environmental conditions so that they are not polluted by medical waste because psychologically it can affect patients, and display a good image for the hospital. the. A sense of comfort (comfort) in the waiting room can be achieved through the placement of trash cans in the interior according to their use. Factors that need to be considered such as garbage storage, color, labels, and lighting have a psychological influence to support the creation of a sense of comfort for patients and paramedics in order to increase work efficiency and effectiveness.